PERCEPTIONS OF STUDENTS ON ONLINE ENGLISH LANGUAGE READING ASSESSMENTS – A PRELIMINARY INVESTIGATION - Tsun Derek, Wong Sing (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Past paper drilling has been a core component in the English Language subject of the Hong Kong Diploma of Secondary Education (HKDSE), the university entrance examination in Hong Kong, China. Such drilling is normally done with pen and paper as this resembles the actual examination scenario. Nonetheless, this poses huge administrative costs when it comes to analysis of student work and performance. With such, various online platforms have been developed to allow students to complete past papers online. To investigate students’ perceptions towards using online platforms to complete examination papers, 25 Secondary 6 (Grade 12) students in a Hong Kong secondary school participated in a pilot programme in which they completed a HKDSE reading comprehension paper through an online platform accessed using school-provided Chromebooks in-class. Apart from using an online platform as the means of assessment, all other variables were kept controlled when compared to an actual in-school assessment. After the test, students were given tentative scores and immediate feedback generated through the platform’s auto-marking feature. They were also engaged in a short feedback session explaining their scores, strengths and weaknesses, before further follow-up sessions over the next few days centralizing on extra materials developed based on their weaknesses as identified in through their work. When comparing results from their pre-programme and post-programme surveys and when drawing on the teacher-researcher’s observation notes, findings showed that while initial perceptions of making use of an online platform to complete past papers saw an overall change from negative to positive, feedback was generally mixed in terms of technological requirements, efficiency, educational outcomes and physical demands. Given the increasing importance of digital devices in the modern-day classroom, this paper sheds light on students’ perceptions towards using e-assessment tools and applications in language learning, and holds particular importance in the future development of such platforms.